2007
DOI: 10.1002/cpp.529
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome Questionnaire (OQ‐45) in a Dutch population: A cross‐cultural validation

Abstract: The cross-cultural validity of the Outcome Questionnaire (OQ) in the Dutch population has been examined by comparing the psychometric properties and equivalence in factor structure and normative scores of the Dutch OQ with the original American version. Data were collected from a university (n = 268), in a community (n = 810) and from three mental health care organizations (n = 1920). Results show that the psychometric properties of the Dutch OQ were adequate and similar to the original instrument. Some differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
156
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(196 citation statements)
references
References 30 publications
18
156
0
14
Order By: Relevance
“…However the results for the different subscales were weaker which is in accordance with results of other studies 17,18,34,35 . Further the total score of the OQ-45 was found to predict level of depression and health-related quality of life in patients, beyond demographic characteristics and other instruments.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However the results for the different subscales were weaker which is in accordance with results of other studies 17,18,34,35 . Further the total score of the OQ-45 was found to predict level of depression and health-related quality of life in patients, beyond demographic characteristics and other instruments.…”
Section: Discussionsupporting
confidence: 91%
“…Further the total score of the OQ-45 was found to predict level of depression and health-related quality of life in patients, beyond demographic characteristics and other instruments. Similar to other studies in Europe and USA the results indicate that the total score of the OQ-45 can be of valuable use for clinicians and researcher in the field 17,37,38 . The regression analyses showed that the OQ-45 contributed uniquely to describe the patients' problems.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…À ce jour, aucun tableau normatif spécifique aux populations franco-québécoises, franco-canadiennes ni canadiennes, n'est disponible pour la MI. Par contre, des études de validation de la OQ-45 (version américaine originale de la MI) auprès de populations européennes ont révélé que les propriétés psychométriques de l'instrument traduit sont similaires à la version américaine originale, mais que les normes et les seuils critiques pour évaluer les changements cliniques diffèrent (Chiappelli, Lo Coco, Gullo, Bensi, & Prestano, 2008;Jong et al, 2007). Carter, 2011).…”
unclassified
“…Na amostra holandesa, as distribuições das notas de corte são: Escore Total= 54; Desconforto Subjetivo = 33; Relações Interpessoais = 12; Papel Social = 11. (Jong et al, 2007).…”
Section: Aplicação E Avaliação Do Oq-452unclassified